2018
DOI: 10.1007/s11165-018-9714-y
|View full text |Cite
|
Sign up to set email alerts
|

Board Game in Physics Classes—a Proposal for a New Method of Student Assessment

Abstract: The aim of this study was to examine the impact of assessing students' achievements in a physics course in the form of a group board game. Research was conducted in two groups of 131 high school students in Poland. In each school, the research sample was divided into experimental and control groups. Each group was taught by the same teacher and participated in the same courses and tests before the game. Just after finishing the course on waves and vibrations (school 1) and optics (school 2), experimental group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
1
16
0
3
Order By: Relevance
“…His study revealed that playing the game increased knowledge as students in the experimental group performed better than the control group at the posttest, a week after playing the game. Furthermore, the game made taking the test enjoyable and motivated participants to continue learning (Dziob, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…His study revealed that playing the game increased knowledge as students in the experimental group performed better than the control group at the posttest, a week after playing the game. Furthermore, the game made taking the test enjoyable and motivated participants to continue learning (Dziob, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In their study, games created to explain various concepts such as quantum mechanics principles, time dilation, and nano-biotechnologies were excellent in advancing students' interest and comprehension of these notions (Chiarello & Castellano, 2016). Dziob (2020) used board games to assess Polish students' knowledge in a physics course. His study revealed that playing the game increased knowledge as students in the experimental group performed better than the control group at the posttest, a week after playing the game.…”
Section: Chemistry and Engineeringmentioning
confidence: 99%
“…In order to ensure the optimal effect of collaborative learning, a) the knowledge of group members should not be of the same level, instead, knowledge gaps should be present among members; b) the type of tasks should be of a problem-solving nature, and c) the learning strategy needs to be in line with the learners' level of expertise (Retnowati et al, 2018). Correspondingly, students reported that collaboration allowed them to build on each other's knowledge, develop new attitudes, cognitive and psychomotor skills (Dziob, 2020) but, also, gain confidence in their existing capabilities and stimulated them to apply the knowledge and skills learned in their place of work (Alt & Raichel, 2020). In order to avoid collaboration creating an extraneous cognitive load that can reduce learning, learners need to perceive collaboration as necessary to achieve their learning goal (Chandler & Sweller, 1991).…”
Section: Learning Context and Learning Outcomesmentioning
confidence: 99%
“…Learning that only sitting still listening to explanations without any challenges will make children bored quickly (Murti, 2018;Ratminingsih, 2018). The selection of the right learning media can increase children's interest, attention, and motivation in the teaching and learning process so that children's experiences and skills will increase (Dziob, 2020;Shalikhah, 2017;Taka, 2019). Therefore, the use of learning media that can bring a pleasant atmosphere, stimulate children's activity, and are not hindered by space and time can be the solution, and one of them is board games (Karo-Karo & Rohani, 2018;Putri & Yunianta, 2018;Tauresia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%